Development of CuO-based oxygen carriers supported on diatomite and kaolin for chemical looping combustion (Research, Society and Development, 2021)
Chemical Looping Combustion (CLC) technology has emerged as a promising alternative capable of restricting the effects of global warming due to anthropogenic gas emissions, especially CO2, through its inherent capture. This study aims to synthesize and evaluate Cu-based oxygen carriers supported on natural materials such as diatomite and kaolin, through the incipient wet impregnation method for CLC process applications. Oxygen carriers were characterized by X-ray diffraction (XRD), temperature-programmed reduction (TPR), and scanning electron microscopy with surface energy dispersive x-ray spectroscopy (SEM-EDS). The mechanical strength of the two oxygen carrier particles was determined after the sintering procedure resulting in high crushing force. Reactivity of oxygen carriers was evaluated in a thermobalance with CH4 and H2 gases. Different reaction pathways were attempted when undergoing the redox cycles: total direct reduction of CuO to Cu0 for Cu-K and partial reduction of CuO to Cu2O and CuO to Cu-D. However, the highest reactivity and reaction rate was achieved in Cu-D due to the pore structure of diatomite, the chemical composition and the resulting interaction between CuO and the support. H2 gas reactivity tests showed a higher conversion rate and greater stability between cycles for both oxygen carriers. Thus, the reducible CuO content present in Cu-Diatomite during the reactivity test with H2 as the fuel gas was ideal for achieving high solids conversion, tendency for greater stability and a higher reaction rate.